Evaluation pro/antioxidant balance in patients with wet form of age-related macular degeneration - Mrowicka, Małgorzata; Mrowicki, Jerzy; Szaflik, Jacek P.; Szaflik, Marta; Ulińska, Magdalena; Szaflik, Jerzy; Majsterek, Ireneusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Objective : The aim of study was to evaluate the ability of the enzymatic antioxidant barrier to protect against peroxidation in patients with wet age-related macular degeneration, as compared to healthy subjects. Material and methods : Hemolysate blood samples collected from 25 patients with wet form age-related macular degeneration and 25 healthy controls were analysed to determine the activity of superoxide dismutase (using Misra and Fridovich method), catalase (using Beers and Sizer method), glutathione peroxidase (using Sedlak and Lindsay method modified by Little and O’Brien), and malondialdehyde concentration (using Placer method). Results : We observed a statistically significant decrease in the activity of following enzymes in patients with wet age-related macular degeneration, as compared to controls: superoxide dismutase (2086.3 vs. 2348.5 U/gHb/100 ml; p ≤ .05), catalase (6.9 vs. 7.6 BU/gHb, p ≤ .05) and glutathione peroxidase (36.3 vs. 45.8 U/gHb; p ≤ .05). At the same time, an increase in age-related macular degeneration thiobarbituric acid reactive substance concentration was demonstrated in patients with wet age-related macular degeneration, as compared to healthy subjects (.119 vs. .286 µmol/gHb; p ≤ .001). Conclusion : The obtained results indicate inefficient enzymatic antioxidant system which manifests as intense peroxidation in patients with age-related macular degeneration.